Tinjauan Faktor Penyebab Daya Tangkap Rendah pada Siswa dalam Proses Pembelajaran di SMP Negeri 35 Medan - Devi Putri Thesia; Elsa Prida Br Tarigan; Eshaulin Br Sembiring; Erbina Br Sembiring; Pebriana Asina Panjaitan; Yosua Gabe Maruli Sijabat; Abdi Nur Batubara (STIKes Ibnu Sina Ajibarang, 2024)
In a teaching and learning process, the level of understanding of a student is very important to the learning material delivered by the teacher in order to achieve the success of the teaching and learning process. If students are unable to understand or find it difficult to understand the material delivered by the teacher, the teaching and learning process will be slightly hampered. Therefore, the student's ability to catch is very important in the teaching and learning process in order to achieve good learning objectives. In this research, the method used is qualitative method. Qualitative methods involve data collection through observation interviews, and document analysis. As for the results of research that has been conducted at SMP Negeri 35 Medan in class VIII-3, there are inhibiting factors that result in low catchability in students such as physical factors, school environment factors and family environment factors.